Medial gastrocnemius and soleus muscle-tendon unit, fascicle, and tendon interaction during walking in children with cerebral palsy - Barber, L.; Carty, C.; Modenese, L.; Walsh, J.; Boyd, Roslyn; Lichtwark, G. (Wiley-Blackwell Publishing Ltd., 2017)
© 2017 Mac Keith Press.Aim: This study investigates the in vivo function of the medial gastrocnemius and soleus muscle-tendon units (MTU), fascicles, and tendons during walking in children with cerebral palsy (CP) and an equinus gait pattern. Method: Fourteen children with CP (9 males, 5 females; mean age 10y 6mo, standard deviation [SD] 2y 11mo; GMFCS level I=8, II=6), and 10 typically developing (6 males, 4 females; mean age 10y, SD 2y 1mo) undertook full body 3D gait analysis and simultaneous B-mode ultrasound images of the medial gastrocnemius and soleus fascicles during level walking. Fascicle lengths were analysed using a semi-automated tracking algorithm and MTUs using OpenSim. Statistical parametric mapping (two-sample t-test) was used to compare differences between groups (p<0.05). Results: In the CP group medial gastrocnemius fascicles lengthened during mid-stance gait and remained longer into late-stance compared to the typically developing group (p<0.001). CP medial gastrocnemius fascicles shortened less during stance (1.16mm [SD 1.47mm]) compared to the typically developing group (4.48mm [SD 1.94mm], p<0.001). In the CP group the medial gastrocnemius and soleus MTU and tendon were longer during early- and mid-stance (p<0.001). Ankle power during push-off (p=0.015) and positive work (p<0.002) and net work (p<0.001) were significantly lower in the CP group. Interpretation: Eccentric action of the CP medial gastrocnemius muscle fascicles during mid-stance walking is consistent with reduced volume and neuromuscular control of impaired muscle. Reduced ankle push-off power and positive work in the children with CP may be attributed to reduced active medial gastrocnemius fascicle shortening. These findings suggest a reliance on passive force generation for forward propulsion during equinus gait.